Pengaruh Pengembangan Karakter Siswa SD PLTU Suralaya Wukir Retawu Kelas VI untuk Berpikir Kritis di Era Generasi Alpha - Dela Ardianti; Desty Endrawati Subroto; Jihan Rohadatul Aisy; Muhamad Dai Azizi; Wulandari Nurhazriyah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The purpose of the study is to examine the relationship between character education and critical thinking so that Generation Alpha will be smart and value-based individuals who are globally competitive. The research methodology of this study used literature analysis. The study revealed that there are three levels of character education: knowing good values, loving good values, and doing good values. Character education is now a force to be reckoned with in shaping individuals of good character and integrity. With the dawn of the current era of digital technology, the influence of social media, global access to information, and technology render more relevant character education even more necessary. Character education process, its hinderances, and how they can be overcome by collective efforts on the part of society, schools, and parents through judicious use of technology are elaborated in this study.